Agronomic and nutritional quality, and fresh and processing attitude, of globe artichoke (Cynara cardunculus L. var. scolymus) cultivars and an Italian landrace. Issue 6 (1st November 2016) - Cappelletti, Roberto; Balducci, Francesca; Diamanti, Jacopo; Mazzoni, Luca; Capocasa, Franco; Battino, Maurizio; Mezzetti, Bruno
ABSTRACT: Globe artichoke ( Cynara cardunculus L. var. scolymus ) plants of a typical landrace ('Montelupone A') from the Marche region (Italy) and three commercial cultivars ('Apollo', 'Romanesco C3', 'Exploter') were compared as a detailed analysis of their productive, morphological, qualitative, and nutritional parameters was carried out to characterise their particularities and suitability for the fresh market or the processing industry. Cultivar 'Apollo' stands out for its qualitative and agronomic aspects, with 'Romanesco C3' showing high flower head yield, as the most important Romanesco cultivar that is widely cultivated in central Italy. 'Exploter' shows high productivity and qualitative characteristics. The lower phenol content of 'Exploter' indicates its suitability for processing as a fresh cut preparation. The 'Montelupone A' landrace is characterised by beneficial nutritional values that indicate its use for fresh consumption and as a source of antioxidant compounds. The 'Apollo' and 'Romanesco C3' commercial cultivars show higher processing yield due to flower head characteristics. In particular, 'Apollo' has an interesting profile according to its technological qualitative and nutritional value. 'Exploter' differs in its high yield and suitability for the fresh market. Analysis of the 'Montelupone A' landrace confirms its interesting qualitative and nutritional values.